Graphene Biotransformation: Biotransformation and Biological Interaction of Graphene and Graphene Oxide during Simulated Oral Ingestion (Small 24/2018). Issue 24 (14th June 2018) - Guarnieri, Daniela; Sánchez‐Moreno, Paola; Del Rio Castillo, Antonio Esaú; Bonaccorso, Francesco; Gatto, Francesca; Bardi, Giuseppe; Martín, Cristina; Vázquez, Ester; Catelani, Tiziano; Sabella, Stefania; Pompa, Pier Paolo
Abstract : In article number1800227, Stefania Sabella, Pier Paolo Pompa and co‐workers analyze the biotransformation and biological interaction of graphene and graphene oxide through an oral ingestion assay simulating chronic exposure. No structural changes/degradation of the nanomaterials are detected during their passage through the gastrointestinal tract, suggesting their biopersistence when administered by oral route. Digested graphene did not affect intestinal barrier integrity, though long‐term adverse effects cannot be excluded.